Clinical and Histopathological Characteristic of Salivary Gland Carcinoma in Dr. Hasan Sadikin General Hospital in 2009â2012 - Andriani, Fatimah Lidya; Nur, Ismet Muchtar; Mahdiani, Sally (Althea Medical Journal, 2016)
Background: Salivary gland neoplasm is one of the rare neoplasm. The frequency of this neoplasm is lower than 2% of all type of tumors in human. Malignant salivary gland tumor comprises 6% of all head and neck tumors. Data about salivary gland carcinoma are still limited. The aim of this study was to determine the frequency of malignant salivary gland based on the patientsâ age, gender, site of lesion and histopathology type. Methods: This study was conducted descriptively. There were 97 subjects found from histopathological form that had been examined in Department of Anatomical Pathology, Dr. Hasan Sadikin General Hospital in 2009â2012. Total sampling technique was used and all data about patientsâ age, gender, site of lesion and histopathology type were collected and analyzed.Results: Of 97 cases, age group 50â59 years old had the highest frequency (29%). The prevalence in male was more frequent than female with male:female ratio was 1.4:1. The most common site of carcinoma was found in parotid gland (45%). Mucoepidermoid carcinoma was the most common histopathology type found in this study (28%).Conclusions: Salivary gland carcinoma is still a rare malignant case in Dr. Hasan Sadikin General Hospital. Carcinoma in parotid gland was the most common site and mucoepidermoid carcinoma was the most common histopathology type. [AMJ.2016;3(1):54â8]DOI:Â 10.15850/amj.v3n1.696